2016
DOI: 10.1016/bs.aambs.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Aggregation and Coagulation Mechanisms, and Their Function in Host–Pathogen Interactions

Abstract: The human commensal bacterium Staphylococcus aureus can cause a wide range of infections ranging from skin and soft tissue infections to invasive diseases like septicemia, endocarditis, and pneumonia. Muticellular organization almost certainly contributes to S. aureus pathogenesis mechanisms. While there has been considerable focus on biofilm formation and its role in colonizing prosthetic joints and indwelling devices, less attention has been paid to non-surface attached group behavior like aggregation and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 223 publications
(300 reference statements)
2
110
0
1
Order By: Relevance
“…S. aureus expresses a range of host matrix binding proteins on its surface in addition to albumin-binding activities (48)(49)(50). One of the albumin-binding proteins, Ebh, has been shown to contribute to survival in blood and the overall pathogenesis of staphylococcal infections (49).…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus expresses a range of host matrix binding proteins on its surface in addition to albumin-binding activities (48)(49)(50). One of the albumin-binding proteins, Ebh, has been shown to contribute to survival in blood and the overall pathogenesis of staphylococcal infections (49).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that some of the cell surface proteins of S. aureus bind and aggregate following interaction with extracellular matrix proteins in the blood (42,43). We previously analyzed the properties of CBPpositive S. mutans strain binding to type I, III, and IV collagens, since these collagen types are major components of cardiovascular tissues (11).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria in different growth modes have distinctly different characteristics. Planktonic refers to free living bacterial cells, which can occur in two forms: as single bacterial cells or in clusters known as planktonic aggregates (Crosby et al 2016). Clinically, this planktonic mode generally refers to bacteria that gain entrance to the human body in the bloodstream and cause bacteremia, which results in acute infections often effectively treated by the host immune system and antibiotics (Stewart and Costerton 2001;Brady et al 2018).…”
Section: Bacteriamentioning
confidence: 99%